Organized synergy as an imperative of integration strategies (based on the study of Russian chemical and petrochemical holdings) - Shevtsova, A.Z. (Економіка промисловості, 2014)
The paper studies the formation of powerful holdings in the Russian chemical and petrochemical industry as well as the latest tendencies on the merges - acquisitions industry market. The industry is being reformed and consolidated; the monopoly structures are created. Strategic synergism plays an important role in these processes. The relevance of this study is high because similar processes are currently undergoing in the Ukrainian chemical industry. The main objective of the current work is to study and summarize the rich Russian experience in implementation of integration strategies in the chemical complex and analyze their synergetic basis. The conducted research proved that the imperative of modern integration strategies in the chemical industry business structures is organizing and implementing different kinds of synergies with the goal of creating a sustainable basis for their competitive advantages in both domestic and global markets. As a result, the large vertically integrated chemical holdings that seek and retrieve the well-known benefits of synergism are formed. It is explored that currently the main trend of M&A industry market is a focused construction of full chains of interrelated business segments. This includes own raw materials base, efficient processing capacities, logistics and distribution networks. It is shown that the acquisition of foreign production assets, transportation and distribution systems and receiving synergetic advantages associated with that is one of the modern tools for advancing on international markets. Synergy-based integration strategies should be considered as a mechanism for creating strong national integrated structures with aim to withstand the global industry giants. The current trend aimed at consolidating the Russian chemical industry should be preserved in the nearest perspective. The Ukrainian chemical assets are still a target for acquisition strategies of Russian holdings.